An Analysis of Pharmacogenomic-Guided Pathways and Their Effect on Medication Changes and Hospital Admissions: A Systematic Review and Meta-Analysis - David, Victoria; Fylan, Beth; Bryant, Eleanor; Smith, Heather; Sagoo, Gurdeep S.; Rattray, Marcus (Frontiers in Genetics, 2021)
Ninety-five percent of the population are estimated to carry at least one genetic variant that is discordant with at least one medicine. Pharmacogenomic (PGx) testing has the potential to identify patients with genetic variants that puts them at risk of adverse drug reactions and sub-optimal therapy. Predicting a patient's response to medicines could support the safe management of medicines and reduce hospitalisation.  These benefits can only be realised if prescribing clinicians make the medication changes prompted by PGx test results. This review examines the current evidence on the impact PGx testing has on hospital admissions and whether it prompts medication changes.   A systematic search was performed in three databases (Medline, CINAHL and EMBASE) to search all the relevant studies published up to the year 2020, comparing hospitalisation rates and medication changes amongst PGx tested patients with patients receiving treatment-as-usual (TAU). Data extracted from full texts were narratively synthesised using a process model developed from the included studies, to derive themes associated to a suggested workflow for PGx-guided care and its expected benefit for medicines optimisation and hospitalisation. A meta-analysis was undertaken on all the studies that report the number of PGx tested patients that had medication change(s) and the number of PGx tested patients that were hospitalised compared participants that received TAU. The search strategy identified 5 hospitalisation themed studies and 5 medication change themed studies for analysis. The meta-analysis showed that medication changes occurred significantly more frequently in the PGx tested arm across 4 of 5 studies. Meta-analysis showed that all-cause hospitalisation occurred significantly less frequently in the PGx tested arm than the TAU. The results show proof of concept for the use of PGx in prescribing that produces patient benefit. However, the review also highlights the opportunities and evidence gaps that are important when considering the introduction of PGx into health systems; namely patient involvement in PGx prescribing decisions and thus a better understanding of the perspective of patients and prescribers.   We highlight the opportunities and evidence gaps that are important when considering the introduction of PGx into health systems.